Cybercrime victimisation and categorization - a view from the perspective of Routine-Activity-Theory (RAT) = Cybercrime-Viktimisierung und Kategorisierung - eine Betrachtung aus der Perspektive der Routine-Aktivitäten-Theorie (RAT) - Huber, Edith (Kriminologie - das Online-Journal, 2025)
This study explores the intersection of cybercrime victimisation and prevention through the lens of Rou-tine Activity Theory (RAT). Using a representative survey in Austria, the research examines the victim-isation experiences of private individuals, focussing on financial, data, and personal cybercrimes. The findings reveal significant differences in demographics and guardianship levels among victims of differ-ent cybercrime types. Notably, higher levels of physical and personal guardianship were unexpectedly correlated with increased victimisation. This study underscores the heterogeneity of cybercrime and the need for nuanced prevention strategies that take into account the distinct characteristics of various cy-bercrime types. The implications highlight the complexity of the relationship between cybersecurity measures and victimisation, challenging assumptions about the protective efficacy of increased cyber-security awareness and measures.